Nursing Home Visits and Elderly Patient Outcomes: A Comprehensive Review - Bushra Saleh Alhassoon et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Nursing home visits—whether social (from family and friends) or clinical (from healthcare providers)—have a profound impact on the physical, cognitive, and emotional well-being of elderly residents. This review synthesizes existing literature on the effects of visitation in nursing home settings, demonstrating that regular and meaningful visits can lead to improved disease management, reduced hospitalizations, slower cognitive decline, and enhanced emotional health. Additionally, barriers to effective visitation, such as pandemic-related restrictions and logistical challenges, are examined. The review concludes with recommendations for enhancing visitation practices to improve health outcomes and quality of life for elderly patients in long-term care. Received Date: July 09, 2024 Accepted Date: July 30, 2024 Published Date: August 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/364 https://doi.org/10.5281/zenodo.15213292